(untitled) (Al-Qamar, 2022)
The study of the Qur’an started very early in the history of the world with multiple objectives. For this purpose, many Orientalists and western researchers have tried to interpret and explain the Holy Qur’an with their background and understanding. This paper deals with the introduction of some major English translations and exegesis of the Holy Qur’an. It intends to trace the western mind through the different English works on Qur’an and their implications for the further study of the Qur’an. The current research written with a descriptive and analytical approach proves that the western scholars have failed to grasp the real meaning and message of the word of Allah. It also proves that biasness and subjectivity is dominant in their study of Qur’an.